Improving the quality of the acoustic environment in neonatal intensive care units: a review of scientific literature and technological solutions - Lenzi, Sara; Spagnol, Simone; Özcan, Elif (Frontiers in Computer Science, 2023)
There is an increased awareness of how the quality of the acoustic environment impacts the lives of human beings. Several studies have shown that sound pollution has adverse effects on many populations, from infants to adults, in different environments and workplaces. Hospitals are susceptible environments that require special attention since sound can aggravate patients’ health issues and negatively impact the performance of healthcare professionals. This paper focuses on Neonatal Intensive Care Units (NICU) as an especially sensitive case representing a hostile acoustic environment in which healthcare professionals have little awareness of how unwanted sounds impact the perceived quality of the soundscape. We performed a semi-systematic review of scientific literature on sound assessment studies in NICU from 2001. A thematic analysis was performed to identify emerging themes that informed the analysis of 27 technological solutions for the assessment of sound quality in indoor and outdoor environments. Solutions were categorized by functions and evaluation methods and grouped according to the characteristics of the design components, i.e., acquisition, computation, and communication strategies. Results highlight a lack of solutions to assess the qualitative characteristics of indoor environments such as NICU and forecast the footprint that different sound sources have on the indoor soundscape. Such solutions are urgently needed to empower healthcare professionals, and especially nurses, to actively modify and prevent the negative impact of unwanted sounds on NICU and critical care soundscape.